2009
DOI: 10.1007/s00253-009-1901-3
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of endoglucanase III (Cel12A) from Trichoderma reesei

Abstract: The stability and specific activity of endo-beta-1,4-glucanase III from Trichoderma reesei QM9414 was enhanced, and the expression efficiency of its encoding gene, egl3, was optimized by directed evolution using error-prone PCR and activity screening in Escherichia coli RosettaBlue (DE3) pLacI as a host. Relationship between increase in yield of active enzyme in the clones and improvement in its stability was observed among the mutants obtained in the present study. The clone harboring the best mutant 2R4 (G41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 27 publications
2
50
2
Order By: Relevance
“…Compared to the kinetic parameters reported by Macarron et al (1993) and Nakazawa et al (2009) for CMCase activity, the K cat value obtained here is higher in comparison to EGIII from T. reesei, with the K m being twice as high. The K m is similar to that found for endoglucanase activity in the crude extract of T. harzianum IOC-3844 (19 g/L) and the endoglucanase from T. harzianum ETS 323 (23 g/L) (de Castro et al, 2010a;Liu et al, 2010).…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…Compared to the kinetic parameters reported by Macarron et al (1993) and Nakazawa et al (2009) for CMCase activity, the K cat value obtained here is higher in comparison to EGIII from T. reesei, with the K m being twice as high. The K m is similar to that found for endoglucanase activity in the crude extract of T. harzianum IOC-3844 (19 g/L) and the endoglucanase from T. harzianum ETS 323 (23 g/L) (de Castro et al, 2010a;Liu et al, 2010).…”
Section: Discussioncontrasting
confidence: 40%
“…Even with a lower degree of thermostability than the EGIII from T. reesei, which displays a high degree of activity until 50°C (Nakazawa et al, 2009), rThEGIII demonstrated stability at temperatures close to the optimal, lasting several days with fairly good activity. Thus, EGIII may be a promising enzyme for the purpose of simultaneous saccharification and fermentation, since this process requires hydrolysis under mild conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TrCel5A has the least homology to the other T. reesei cellulases and has an N-terminal carbohydrate binding module I (16). TrCel12A is smaller (25 kDa) and has no carbohydrate binding module (20), All three are retaining glycoside hydrolases (21,22).…”
Section: ) Endo-14-␤-d-glucan-4-glucanohydrolases (Eg)mentioning
confidence: 99%